Developing a performance story report: user guide - and Roughly, A.; Dart, J. (Commonwealth of Australia, 2009)
This report is a nuts and bolts guide to developing a Collaborative Outcomes Report (COR)/ Performance Story Report (PSR) produced by the Australian Government and Jess Dart. It includes practical tips, step-by-step process guides and definitions of key concepts surrounding these approaches.